What is metacognitive reflection? The moderating role of metacognition on emotional regulation and reflection - Merkebu, Jerusalem; Kitsantas, Anastasia; Durning, Steven J.; Ma, TInglan (Frontiers in Education, 2023)
This paper explores the trilateral relationship among metacognition, emotional regulation, and reflection under the integrative framework of metacognitive reflection. Data were gathered from undergraduate participants at a large state university on the East Coast (N = 493). The quantitative data were derived from: the Metacognitive Awareness Inventory (MAI), the Self-Reflection and Insight Scale (SR-IS), and the Cognitive Reappraisal Scale (ERQ). Data analysis consisted of structural equation modeling (SEM) in which the associations between latent constructs were tested. Emotional regulation and metacognition were found to be positively and significantly related to the latent construct of reflection. SEM results indicated that emotional regulation (which emerged as the strongest predictor) together with metacognition predicted 52% of the variance in reflection. Moreover, the latent moderation model showed that metacognition significantly moderated the relationship between emotional regulation and reflection such that emotional regulation was a strong and positive predictor of reflection when students simultaneously showed high levels of metacognition. In contrast, emotional regulation did not significantly predict reflection for students with low levels of metacognition. The alternative model showed that emotional regulation also moderated the relationship between metacognition and reflection such that metacognition contributed to reflection the most when participants simultaneously showed high levels of emotional regulation. These findings suggest the interaction between metacognition and emotional regulation is critical in the gamut of reflection.